THE MIDDLE AGES IN POLLEN-ANALYTICAL RESEARCH ON THE TERRITORY OF THE CZECH REPUBLIC - Jankovská, Vlasta (Bulletin of Geography. Physical Geography Series, 2011)
An orientation survey of mostly the author’s own results of pollen analyses of medieval sediments from archaeological sites in the Czech Republic is presented. The aim of the several-year-long cooperation with archaeologists was to find out whether, and to what extent, the results of pollen analysis are able to specify more exactly the outcomes of archaeological research. Existing pollen-analytical results confirmed their potential to contribute to interdisciplinary archaeological-archaeobotanical research. From a pollen-analytical perspective it was possible to distinguish early medieval material from high medieval material, particularly in the area of larger medieval towns. Selected finds of palynomorphs (pollen grains, spores and Non-Pollen-Palynomorphs) are mentioned in more detail in the chapters “Botany and pharmacy”, “Hygiene and social situation”, “Problems of the age, function and/or disappearance of some archaeological features and situations” and “Pollen analysis and history”.